2020
DOI: 10.1021/acsomega.0c03977
|View full text |Cite
|
Sign up to set email alerts
|

Coal Dust-Induced Systematic Hypoxia and Redox Imbalance among Coal Mine Workers

Abstract: Continuous inhalation of coal dust among coal workers leads to a variety of disorders. The present study aims to evaluate the potential oxidative stress associated with coal dust generated from coal mining activities among exposed workers through the antioxidant enzyme system, including superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH). In this study cohort, intensive coal mine workers were assessed for antioxidant variations. Blood samples were collected from dust-exposed workers (engaged in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…On the other hand, OP GSH and OP DTT are driven by the contents of organic matter and, probably, water from condensation or spraying, Mg, Na and Ba. A number of studies are in accordance with prior studies which found a relevant role of organic matter and/or moisture Ca species, Mg, Na and Ba of dust in ROS generation (Alcala-Orozco et al, 2020;Attfield and Morring, 1992;Barraza et al, 2020;Castranova and Vallyathan, 2000;Charrier and Anastasio, 2012;Cheng et al, 2021;Gao et al, 2020;Huang et al, 2005Huang et al, , 1998Iram Batool et al, 2020;Maclaren et al, 1989;Nishita-Hara et al, 2019;Xu et al, 2017;Yu et al, 2018).…”
Section: Multilinear Regression Analysis Of the Oxidative Potential O...supporting
confidence: 89%
“…On the other hand, OP GSH and OP DTT are driven by the contents of organic matter and, probably, water from condensation or spraying, Mg, Na and Ba. A number of studies are in accordance with prior studies which found a relevant role of organic matter and/or moisture Ca species, Mg, Na and Ba of dust in ROS generation (Alcala-Orozco et al, 2020;Attfield and Morring, 1992;Barraza et al, 2020;Castranova and Vallyathan, 2000;Charrier and Anastasio, 2012;Cheng et al, 2021;Gao et al, 2020;Huang et al, 2005Huang et al, , 1998Iram Batool et al, 2020;Maclaren et al, 1989;Nishita-Hara et al, 2019;Xu et al, 2017;Yu et al, 2018).…”
Section: Multilinear Regression Analysis Of the Oxidative Potential O...supporting
confidence: 89%
“…Reactive oxygen species (ROS) or free radicals damage the tissues and biomolecules, progressing to various diseases, especially degenerative diseases (cardiovascular disorders, diabetes, endothelial dysfunction, etc.) . Multiple synthetic drugs exhibit substantial protection against oxidative stress/damage, but they have many adverse effects like cardiovascular diseases, hepatotoxicity, nephrotoxicity, and gastrointestinal tract problems. , Alternative options for safer use are the consumption of traditional medicine, natural antioxidants from food supplements, and herbal and polyherbal formulations .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the kidney is the main target organ for heavy metal accumulation ( 4 ). Batool et al ( 5 ) report that coal mine dust can cause inflammation and oxidative damage to miners. Except heavy metal elements, exhaust gases cause oxidative damage ( 6 ).…”
Section: Introductionmentioning
confidence: 99%